Analytical assessment of heterocyclic co pound degrading ability of carbazole degrading marine bacteria - Halimah, binti Ahad (Universiti Malaysia Sarawak (UNIMAS), 2012)
Carbazole is a significant environmental pollutant and not a biodegradable compound that has impact environment and human health. This project was conducted to examine the ability of marine CAR -degrading bacteria from marine environment in the carbazole degradation rate analysis. The isolated strains M02 of Thalassospira projimdimaris was obtained from previous undergraduate student. M02 was enriched with ONR7a liquid media before proceed to other processes. The isolated strain was cultured with [0.1 %] of carbazole in 14 days and the sample was taken on every two days from day two to the day 14. Degradation of the compound. was quantified by using Gas Chromatography-Mass Spectroscopy (GC-MS) method after the extraction with combination of Dichloromethane and Ethyl acetate chemical substances. CFU numbers increase as the concentration of the substrate increase from 0.1 % to 0.7%. Biphenyl shown positive of growth in different substrate test compared to fluorene, dibenzofuran and dibcnzothiophene.